The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/7521601
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Ginsenoside Rg3 via NF-κB Pathway in A549 Cells and Human Asthmatic Lung Tissue

Abstract: Objective. There is limited information of the anti-inflammatory effects of Rg3 on inflamed lung cells and tissues. Therefore, we confirmed the anti-inflammatory mechanism of ginsenoside Rg3 in inflamed human airway epithelial cells (A549) and tissues whether Rg3 regulates nuclear factor kappa B (NF-κB) activity. Methods. To induce the inflammation, IL-1β (10 ng/ml) was treated to A549 cells for 4 h. The effects of Rg3 on NF-κB activity and COX-2 expression were evaluated by western blotting analysis in both I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 59 publications
1
45
0
1
Order By: Relevance
“…2) are the main bioactive dammarane triterpenoids derived from the rhizomes of many plants including Panax notoginseng (Burk.) F. H. Chen, Panax ginseng and Cinnamomum cassia Presl., with various biological effects including anti-oxidative, anti-inflammatory, and anti-cancer activities [219][220][221][222]. Ginsenosides mainly exert anti-cancer effects in colorectal, breast, liver and lung cancers, through inhibiting cell proliferation and migration, angiogenesis, and reversing drug resistance [7,[223][224][225][226][227][228][229][230].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…2) are the main bioactive dammarane triterpenoids derived from the rhizomes of many plants including Panax notoginseng (Burk.) F. H. Chen, Panax ginseng and Cinnamomum cassia Presl., with various biological effects including anti-oxidative, anti-inflammatory, and anti-cancer activities [219][220][221][222]. Ginsenosides mainly exert anti-cancer effects in colorectal, breast, liver and lung cancers, through inhibiting cell proliferation and migration, angiogenesis, and reversing drug resistance [7,[223][224][225][226][227][228][229][230].…”
Section: Ginsenosidesmentioning
confidence: 99%
“…In contrast, the ginsenosides Rh1, Rh2, Rg1, and Rg3 have been reported to inhibit allergic responses [32][33][34][35]. Furthermore, Rg3 has been reported to reduce inflammatory responses in human asthmatic airway epithelial cells and tissues [35]. Consistent with these reports, we found that FPG showed lower levels of Rb1, Rb2, and C-K and had enhanced anti-allergic effect compared to PG and that the levels of Rh1, Rh2, and Rg3 were higher in FPG than in PG.…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, the ginsenosides Rb1, Rd, F2, and compound K (C-K) were reported to induce β-hexosaminidase release from RBL-2H3 cells [3]. In contrast, the ginsenosides Rh1, Rh2, Rg1, and Rg3 have been reported to inhibit allergic responses [32][33][34][35]. Furthermore, Rg3 has been reported to reduce inflammatory responses in human asthmatic airway epithelial cells and tissues [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ginsenoside Rg3 significantly reduced chloroquine-induced scratching in mice. Lee et al reported that ginsenoside Rg3 inhibited NF-κB activation and COX-2 expression in IL-1β-stimulated human asthmatic airway epithelial tissues [79]. Ginsenoside Rh2 attenuates allergic airway inflammation in ovalbumin-sensitized mice by regulating NF-κB activation and p38 MAPK phosphorylation [80].…”
Section: Anti-allergic Effects Of Ginseng Constituentsmentioning
confidence: 99%